Comparative study lumbar plexus block and lumbar erector spinae plane block for postoperative pain relief after proximal femoral nail for proximal femoral fractures - Sandeep Diwan; Abhishek Lonikar; Himaunshu Dongre; Parag Sancheti; Abhijit S Nair; Suhrud Panchawagh (Saudi Journal of Anaesthesia, 2023)
Background: The clinical outcomes (time to ambulation, length of stay, and home discharge) after proximal femoral nail (PFN) for proximal femoral fractures (PFF) is dependent on successful pain management. Currently, the lumbar erector spinae plane block (LESPB) is in vogue and is associated with favorable outcomes in the postoperative period. Our study aimed to evaluate whether a LESPB provided equivalent analgesia and clinical outcomes as compared to LPB in PFN for PFF. Material and Methods: We compared LPBs [L] with LESPBs [E], with 30 patients in each group, performed from June 2020 to June 2021 for PFN in PFF's. The primary outcome of this study was the average NRS pain scores over 24 hours postoperatively. Secondary outcomes included pain scores at different time points over 24 hours, opioid consumption between the groups at 24 hours postoperatively, time for request of first parenteral analgesia, quadriceps weakness and adverse events. Results: The average pain scores over 24 hours were better in the LESPB group as compared to the LPB group (p = 0.02). Further, only n = 5 (30%) of patients in the LESPB group required opioids, while n = 13 (43.333%) of patients in the LPB group required opioids. Moreover, the median time for request of first parenteral analgesia was 615 (480–975) minutes, weakness of quadriceps function occurred in 2 patients in the L group, which recovered at 3rd and 5th month, respectively, with no incidences of hemodynamic instability and respiratory complications. Conclusions: This trial demonstrated that single bolus LESPB is superior to LPB in terms of analgesic outcomes, has low adverse events, and is an agreeable substitute for patients with PFF undergoing a PFN.